Propagation Characteristics in a Circular Waveguide for Feasibility Study of Terabit DSL - Liang, Kar Yan; Che Seman, Fauziahanim; Yee, See Khee; Ahmed Sohoo, Arslan (Journal of Electronic Voltage and Application, 2022)
Due to the demand for higher data rates and greater download speeds by users and increasing number of deployed devices providing content-rich data, new cost-effective technologies which utilizes the concept of waveguides over copper that can enable the realization of terabit DSL need to be explored to meet the required demands. This paper presents the propagation characteristics of circular waveguide which include reflection/transmission coefficient, attenuation coefficient and surface current. The design and simulation process have been carried out using CST Microwave Studios at the frequency of 100GHz to 300GHz. The circular waveguide is varied for various radius and length to observe for the respective propagation characteristics. Based on the result, it is shown that the reflection coefficient decreases with the increase in radius and length and it is below -50dB. Besides, with the increase in frequency, the transmission coefficient shows that the waveguide is able to achieve 100% transmission (0dB) at 200GHz with the increase in radius and length. Moreover, the attenuation coefficient of the waveguide is low which is about 0.0022dB/mm and maximum surface current intensity of 81.5556A/m. The results obtained can be considered the first step on understanding the propagation characteristics of waveguide at terahertz frequency range towards the realization of Terabit DSL.